2009
DOI: 10.1021/ef900051r
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Oxygen-Containing Functional Groups in Liquid-Phase Adsorption of Nitrogen Compounds on Carbon-Based Adsorbents

Abstract: The carbon-based adsorbents are promising for adsorptive denitrogenation (ADN) of liquid hydrocarbon streams. The objective of the present study is to develop a fundamental understanding of the role of surface oxygen-containing functional groups on carbon-based adsorbents in adsorption of nitrogen compounds that are known to be present in liquid fuels. The adsorption properties of four representative activated carbons were evaluated in a batch adsorption system for removing quinoline and indole respectively fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 29 publications
3
78
0
Order By: Relevance
“…This may because of the anode layer of this study was filled with GAC while the anode of the researches mentioned before were made of carbon paper, carbon fibre or carbon felt, and the anode chamber of these researches were filled with liquid. Studies have confirmed that the surface oxygen-containing groups of activated carbon can affect the catalytic performance and change the oxidation-reduction characteristic and promote the reduction reaction (Almarri et al, 2009). In this study, no 1, 4-Benzenediamine, N-methyl-or PPD were detected in the bottom layer despite there was DMPD existence.…”
Section: The Degradation Of Mo Decolorization Productssupporting
confidence: 55%
“…This may because of the anode layer of this study was filled with GAC while the anode of the researches mentioned before were made of carbon paper, carbon fibre or carbon felt, and the anode chamber of these researches were filled with liquid. Studies have confirmed that the surface oxygen-containing groups of activated carbon can affect the catalytic performance and change the oxidation-reduction characteristic and promote the reduction reaction (Almarri et al, 2009). In this study, no 1, 4-Benzenediamine, N-methyl-or PPD were detected in the bottom layer despite there was DMPD existence.…”
Section: The Degradation Of Mo Decolorization Productssupporting
confidence: 55%
“…Adsorptive denitrogenation and desulphurization is considered promising methodology when compared with the conventional hydrodenitrogenation and hydrodesulphurization process, because it can be run at ambient conditions without using hydrogen and catalysts [32]. The importance of denitrogenation process results from the fact that although nitrogen compounds are present at low concentrations, they play an important role in the quality of oil products.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have explored environmental friendly and low cost materials as precursors to prepare ACs that presented high apparent specific surface areas and good performance when tested as adsorbents for nitrogen compounds [32,38].Examples of these materials are biochars from the pyrolysis or combustion of biomasses. The possibility of producing carbon materials with high specific surface areas and micropore volume allied with a considerable surface reactivity make these materials adequate for a great number of applications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Upon combustion of nitrogen-containing fuels, toxic nitrogen oxides are released that cause air pollution. The adsorption of aromatic N-heterocyclic compounds from liquid fuels was studied on zeolites, activated carbons, 4 and novel sorbents such as ionic liquids. 5 Metal−organic frameworks (MOFs) have a very high surface area and pore volume and are well suited for adsorption.…”
Section: Introductionmentioning
confidence: 99%